2017
DOI: 10.29252/ijrm.15.11.687
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a positive reappraisal coping intervention and problem-solving skills training on coping strategies during waiting period of IUI treatment: An RCT

Abstract: Background:Waiting period of fertility treatment is stressful, therefore it is necessary to use effective coping strategies to cope with waiting period of intrauterine insemination (IUI) treatment.Objective:The aim of this study was comparing the effect of the positive reappraisal coping intervention (PRCI) with the problem-solving skills training (PSS) on the coping strategies of IUI waiting period, in infertile women referred to Milad Infertility Center in Mashhad.Materials and Methods:In this randomized cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…Similar success of psychological interventions aimed at improving the coping of infertile women and relieving their distress were reported in two studies in Iran. [31,32] Concerning the narcissistic personality, the current study results revealed generally high pre-intervention scores in most of its domains. This reflects infertile women's response to their inability to conceive by trying to invest onto the self in order to regulate their self-esteem.…”
Section: Discussionmentioning
confidence: 48%
“…Similar success of psychological interventions aimed at improving the coping of infertile women and relieving their distress were reported in two studies in Iran. [31,32] Concerning the narcissistic personality, the current study results revealed generally high pre-intervention scores in most of its domains. This reflects infertile women's response to their inability to conceive by trying to invest onto the self in order to regulate their self-esteem.…”
Section: Discussionmentioning
confidence: 48%
“…These results may be attributed to the fact that this intervention study that was conducted to educate patients undergoing artificial insemination about coping strategies, researchers held a few sessions apart from outpatient setting, and this was effective for specific coping strategies for patients. 14 However, the education and care program of this study contributes to maintaining a good relationship between patients and medical staff by dedicating a small amount of time to frequently collaborate with doctors and nurses regarding daily medical care.…”
Section: Program Outcomesmentioning
confidence: 99%
“…Recently, many randomized controlled trials have been conducted with programs that impose group session or homework; however, most of them are aimed at patients undergoing assisted reproductive technology and are provided by researchers other than clinic medical staff. [12][13][14][15][16] Infertility treatment is divided into non-assisted reproductive technology (non-ART) infertility treatments and assisted reproductive technology (ART). In Japan, government subsidies cover some ART, though it is mainly a self-financed medical treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, besides the waiting time in IVF treatment, the PRCI was used recently during the waiting period of intrauterine insemination treatment30 and as an intervention for pregnant women with a miscarriage history 31 32…”
Section: Introductionmentioning
confidence: 99%